Modeling of air braking process of 20 000 ton heavy haul train - WANG Qingyuan; ZHAO Zining; LIU Qiangqiang; WANG Kaiyun; RAO Yu; SUN Pengfei (机车电传动)
In view of the limited accuracy of the traction calculation method specified in the code for train traction calculation in solving the air braking process of 20 000 ton heavy haul combined trains, based on the existing air braking calculation model of traction gauge, an air braking process solution method suitable for long marshaling heavy haul combined trains was put forward. Firstly, by analyzing the limitations of the traction gauge model and based on the dynamic behavior of the air braking system, the air braking process of heavy haul train was described as idling stage, braking force establishment transient stage and braking force stability steady-state stage according to the time node. Secondly, considering the influence of historical handling behavior on the current air braking performance, the air braking performance correction function was introduced; considering the influence of train formation form on brake wave distribution and brake wave transmission, the brake shoe pressure distribution function of combined train was introduced. Then, based on the basic calculation method of traction gauge air braking force and considering the continuity of air braking force distribution in the whole braking process, a three-stage refined air braking force calculation model was summarized. Finally, based on the actual operation data of 20 000 ton heavy haul train, the model error evaluation function was defined, and the correctness and effectiveness of the refined model were demonstrated by comparing with the existing traction gauge model. The results show that the model has good adaptability under the conditions of single short ramp braking and long downhill cyclic braking of heavy haul train.